Degradation of Methoxylated Benzoic Acids by a Nocardia from a Lignin-Rich Environment: Significance to Lignin Degradation and Effect of Chloro Substituents - Crawford, R. L. (1973)
Strain A81 of Nocardia corallina hydroxylates or demethylates p-anisic acid to p-hydroxybenzoic acid and isovanillic acid. It demethylates veratric acid to a mixture of vanillic and isovanillic acids. These are both demethylated to protocatechuic acid, which undergoes ring cleavage to afford β-carboxy-cis-cis-muconic acid. The intermediacy of protocatechuic acid in the catabolic pathway of veratric acid was confirmed by blocking ring cleavage with an additional substituent in the ring: 5-chlorovanillic acid was demethylated to 5-chloro-protocatechuic acid, which accumulated. Chloro substituents in the ring of other methoxylated benzoic acids also arrested their normal metabolism by the Nocardia: an ortho-chloro substituent thwarted both demethylation and ring-opening. ortho-Hydroxylation of p-methoxybenzoic acid to isovanillic acid was unaffected by a chlorine ortho to the methoxyl group. Washed whole cells of veratric acid-grown N. corallina A81 produced no detected structural changes in an isolated lignin. The implications of this observation are discussed.